Modulation of STAT6 signaling for hepatoprotection - Somm, Emmanuel; Rahman, Mahdi; Szanto, Ildiko; Gariani, Karim; Jornayvaz, François R. (Frontiers in Pharmacology, 2025)
Signal transducer and activator of transcription (STAT) proteins are a family of seven transcription factors mediating various biological processes. STAT6 is classically known to regulate immune cell biology by transmitting signals from interleukin (IL)-4 and IL-13 into transcriptional activation of genes driving type 2 immunity. In orchestrating T helper lymphocytes and macrophages polarization, STAT6 plays a central role in the regulation of both cellular and humoral immunities. Several pathologies, including inflammatory disorders, autoimmune/allergic diseases, metabolic syndrome as well as cancer, are associated with a dysregulation of type 2 immunity related to inadequate expression and/or activity of STAT6. In the present review, following a brief introduction of STAT6 biology, we summarize the immunologic and physiological roles of STAT6 in the context of liver integrity as well as the potential roles of STAT6-mediated pathways in both hepatoprotection and liver pathophysiological mechanisms.